Pharmacy students' knowledge and perceptions about pharmacovigilance in Malaysian public universities - Elkalmi, Ramadan Mohamed; Hassali, Mohamed Azmi; Ibrahim, Mohamed Izham M; Widodo, Riyanto T; Efan, Qais MA; Hadi, Muhammad Abdul (American Association of Colleges of Pharmacy (AACP), 2011)
Objective. To assess senior pharmacy students’ knowledge of and perceptions about pharmacovigilance and reporting of adverse drug reactions (ADRs) at 5 public universities in Malaysia